Relevance of Preeclamsia with Presence of Death of Pregnant Mothers - Putri, Citra Puspita; Rivai, Fitrahayu; Alibugis, Icha Patricia; Latif, Ismiwahyuni; Afrianty, Nanda; Ali, Rahmawatiansi; Panantu, Zianhastika; Husain, Safania R; Lanangawa, Perlanda S; Umar, Sri Mutia; Tanaeyo, Santika; Adam, Sindi Pratiwi (Politeknik Kesehatan Kementrian Kesehatan Gorontalo, 2022)
Maternal Mortality Rate (MMR) is one indicator to see the health status of women. There are two categories of maternal deaths, namely those caused by direct obstetric causes, namely deaths caused directly by pregnancy and childbirth, and deaths caused by indirect causes, namely deaths that occur in pregnant women caused by disease and not by pregnancy or childbirth. Pre-eclampsia and eclampsia are one of the complications of pregnancy that are caused directly by pregnancy itself. Pre-eclampsia is the onset of hypertension accompanied by proteinuria due to pregnancy, after 20 weeks of gestation or immediately after delivery. This study aims to determine the relevance of pre-eclampsia with the percentage of maternal mortality. This research is a literature study that summarizes some of the relevant literature. Articles were searched using the google scholar database, ScienceDirect, MDPI. After screening, 25 articles met the requirements and met the criteria. There is an relevance of pre-eclampsia with the percentage of maternal mortality. It is hoped that the results of this study will be one of the materials for midwifery education and interventions that can be applied in health services in preventing pre-eclampsia.